Unlocking evidence - Singh-Landa, Charanjit; Ramjohn, Mohamed (Abingdon, Oxon [England] : Routledge, 2013)
'Unlocking Evidence will ensure that you grasp the main concepts with ease providing you with an indispensable foundation in the subject. The book explains in detailed, yet straightforward, terms: The burdens and standards of proof Testimony of witnesses; Disclosure of evidence and protection from disclosure; privilege and public interest immunity Course of trial Hearsay Confessions and other illegally obtained evidence Evidence of bad character in criminal proceedingsAdmissibility of bad character evidence of defendants Corroboration, lies, care warnings and identification evidence Opinion, documentary and real evidenceThis second edition is fully up-to-date with the latest changes in the law and now includes discussion of witness anonymity, an expanded section on special measures, more detail on illegally obtained evidence, plus discussion of the context of the law, such as an increasing emphasis on victims. The Unlocking the Law series is designed specifically to make the law accessible. Each chapter opens with a list of aims and objectives, contains activities such as quick quizzes and self-test questions, key facts charts to consolidate your knowledge, and diagrams to aid learning. Cases and judgments are prominently displayed, as are primary source quotations. Summaries help check your understanding of each chapter, there is a glossary of legal terminology. New features include problem questions with guidance on answering, as well as essay questions and answer plans, plus cases and materials exercises.'--
'Unlocking Evidence brings the law to life with diagrams, key facts charts and activities to ensure that you engage with, and fully understand, evidence'--
The law of evidence : the burdens and standards of proof -- Testimony of witnesses -- The disclosure of evidence and protection from disclosure : privilege and public interest immunity -- Silence : the effect on an accusation -- Course of trial -- Hearsay : the exclusionary rule -- Hearsay : admissibility in criminal cases -- Hearsay : civil cases -- Confessions and evidence obtained unlawfully -- Evidence of bad character in criminal proceedings -- Admissibility of bad character evidence of witnesses and defendants -- Corroboration, lies, care warnings and identification evidence -- Opinion, documentary and real evidence.
Keywords: Evidence (Law) -- Great Britain